STUDENTS’ PERCEPTIONS ON THE USE OF TIKTOK IN LEARNING SPEAKING SKILLS - Syarmila Syarmila; Selfa Yurnita; Ahmad Jailani (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2023)
There are a lot of media available today that can be utilized for education. Using TikTok, a social media platform, is one approach to speak English on your own. This study aims to investigate students' perceptions of TikTok as a medium for learning English. This study employs a descriptive qualitative approach. Researchers employed interviews to gather data. This study's participants are students majoring in English education, consisting of 5 participant taken by purposive sampling. This research reveals that TikTok provides students with the opportunity to watch English-language videos created by native speakers, which can improve their listening skills, expand their vocabulary, improve their grammar and pronunciation, and introduce them to variations in English accents. TikTok can also help students develop their overall English skills in a fun and dynamic way. However, for TikTok to be used effectively as an English learning tool, it requires help from teachers and good content management.